Case Report: Pirfenidone in the Treatment of Post-COVID-19 Pulmonary Fibrosis - Zhou, Xianglin; Yang, Danhui; Kong, Xianglong; Wei, Chengli; LvQiu, Siqi; Wang, Lin; Lin, Yongkang; Yin, Zhilan; Zhou, Zhiguo; Luo, Hong (Frontiers in Medicine, 2022)
Background Pulmonary fibrosis is one of the sequelae of the COVID-19, which seriously affects the quality of life of survivors. Currently, there are no optimal evidence based guidelines targeting this population. Case Presentation We report a 66-year-old female patient without underlying comorbidities admitted to Changsha Public Health Center because of COVID-19. During hospitalization, she developed co-bacterial infection and acute respiratory distress syndrome, and received broad-spectrum antibacterial therapy, invasive mechanical ventilation and extracorporeal membrane oxygenation. After the acute phase, she developed post-COVID-19 pulmonary fibrosis subsequently treated with pirfenidone. Over 96 weeks after pirfenidone treatment, her modified Medical Research Council Dyspnea level improved to 2 from 4 at discharge. Her 6 minutes walk test distance, total lung capacity, and diffusion capacity for carbon monoxide all increased. Chest CT performed on 2 years after illness onset showed regressing fibrosis. The Hospital Anxiety and Depression Scale, Athens Insomnia Scale, and 36-Item Short Form Health Survey questionnaire all improved. Conclusion Post-COVID-19 pulmonary fibrosis is a challenging consequence of COVID-19, and our case suggests that pirfenidone may be an effective treatment option.